2010
DOI: 10.1111/j.1365-2982.2010.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and vasoactive intestinal peptide are reduced in right transverse colon in pediatric slow‐transit constipation

Abstract: There are age-related reductions in nerve fiber density in human colon circular muscle. NOS and VIP do not show regional variations, while SP nerve fiber density is higher in distal colon. 1/3 of pediatric STC patients have low SP or VIP nerve fiber density in proximal colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 93 publications
2
43
0
Order By: Relevance
“…52 Often, the pressure required is found to be higher than in subjects with normal colonic transit. 53 Various physiologic and histobio-chemical findings have been postulated to explain the phenomenon of slow colonic transit: reduced cholinergic 54,55 and enhanced adrenergic responses 55 ; mitigated gastrocolic reflex 56 ; dysynergy of rectosigmoid colonic activities 57,58 ; enteric neurodegeneration 59 of both the myenteric plexus ganglia 60,61 and the interstitial cells of Cajal 61,62 ; and abnormalities of enteric neurotransmitters such as substance P, [63][64][65] vasoactive intestinal peptides, 63,64 and nitric oxide.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…52 Often, the pressure required is found to be higher than in subjects with normal colonic transit. 53 Various physiologic and histobio-chemical findings have been postulated to explain the phenomenon of slow colonic transit: reduced cholinergic 54,55 and enhanced adrenergic responses 55 ; mitigated gastrocolic reflex 56 ; dysynergy of rectosigmoid colonic activities 57,58 ; enteric neurodegeneration 59 of both the myenteric plexus ganglia 60,61 and the interstitial cells of Cajal 61,62 ; and abnormalities of enteric neurotransmitters such as substance P, [63][64][65] vasoactive intestinal peptides, 63,64 and nitric oxide.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…In addition, both a reduction in the density of tachykininimmunoreactive nerve fibres in human colonic circular muscle (Porter et al, 1998) and decreases in tachykininsignalinghavebeen observed in patients with slow transit constipation consistent with tachykinins having apro-kinetic effect. (King et al, 2010;Stanton et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thinking that proximal muscle biopsies would be needed to identify an intrinsic motility disorder, we began offering laparoscopic biopsy to patients with intractable constipation. This identified a subgroup of patients where there was abnormality of neuropeptide labelling of the nerves supplying the circular muscle [7][8][9][10]. At the time, it was not known whether the abnormal staining (deficiency of Substance P immunoreactivity) was primary or secondary, but it did suggest these children had an intrinsic organic disorder.…”
Section: Introductionmentioning
confidence: 92%